Outside Back Cover: Volume 2 Issue 4. (22nd December 2021) - Li, Tingzhen; Peng, Xinwen; Cui, Peng; Shi, Ge; Yang, Wu; Chen, Zehong; Huang, Yongfa; Chen, Yongkang; Peng, Jinyuan; Zou, Ren; Zeng, Xiaoyan; Yu, Jian; et al.
Abstract : Outside back cover image : Recent Progress and Future Perspectives of Flexible Metal‐air Batteries Xinwen Peng and Jun Lu summarized the recent research progress of flexible metal‐air batteries together with their remaining technical barriers. They highlighted how the gel polymer electrolytes and flexible electrodes with different components or structural types affect the operational performance of flexible metal‐air batteries, especially for flexible Zn‐ and Li‐air batteries. The future development perspectives of flexible metal‐air batteries for wearable and smart electronics were also given. (DOI: https://doi.org/10.1002/smm2.1076 )